Towards a model of uncertainty distress in the context of Coronavirus (COVID-19). (2020) - Freeston, Mark; Tiplady, Ashley; Mawn, Lauren; Bottesi, Gioia; Thwaites, Sarah
Abstract: The paper forms part of a series of papers outlining the theoretical framework for a new model of uncertainty distress (this paper), treatment implications arising from the model, and empirical tests of the model. We define uncertainty distress as the subjective negative emotions experienced in response to the as yet unknown aspects of a given situation . In the first paper we draw on a robust body of research on distinct areas including: threat models of anxiety, perceived illness uncertainty and intolerance of uncertainty. We explore how threat and uncertainty are separable in anxiety and how we can understand behaviours in response to uncertainty. Finally, we propose a clinically, theoretically and empirically informed model for uncertainty distress, and outline how this model can be tested. Caveats, clinical applications and practitioner key points are briefly included, although these are more fully outlined in the treatment implications article. While we outline this model in the context of novel coronavirus (COVID-19), the model has broader applications to both mental and physical health care settings. Key learning aims: (1) To define the concept of uncertainty distress. (2) To understand the role of threat, over-estimation of threat, perceived uncertainty, actual uncertainty, and intolerance of uncertainty in distress maintenance. (3) To understand how people may behave in response to uncertainty distress. (4) To describe a model of uncertainty distress.